Psychological factors in the development of social-emotional competencies of primary school children - Rahmatova Nasiba Sobirovna (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the psychological factors that influence the development of social-emotional competencies in primary school children, emphasizing the role of empathy, self-regulation, cooperation, decision-making, and social responsibility in shaping personal growth and adaptability. Research Methodology: A qualitative and descriptive design was employed using questionnaires, interviews, observations, reflection diaries, and role-play tasks. The methods were applied to evaluate how family environment, school context, and teacher-student interactions affect children’s emotional-volitional qualities and social skills. Results: Findings demonstrate that social-emotional competencies form an integrated system rather than isolated abilities. Children with stronger empathy and self-regulation exhibit better cooperation and decision-making, leading to higher academic success and resilience. Environmental determinants—family support, classroom climate, and peer relations—emerged as decisive factors for strengthening these competencies. Structured interventions such as emotional literacy training and cooperative learning tasks were found to significantly enhance self-awareness, emotional control, and interpersonal relationships. Conclusions: The development of social-emotional competencies is central to holistic child development. Schools, families, and psychological services must collaborate to systematically integrate social-emotional learning into educational practice, ensuring sustainable academic and personal outcomes. Limitations: The study mainly focuses on psychological and educational settings in primary schools, without large-scale quantitative validation across broader populations. Contribution: This research contributes to educational psychology by providing practical recommendations for integrating social-emotional learning strategies, offering insights for teachers, parents, and policymakers to foster resilience and life skills in children.